Tracing our Italian roots - Lee, Kathleen (Santa Fe, N.M. : J. Muir Publications ; New York : Distributed to the book trade by W.W. Norton ; Bothell, WA : Distributed to the education market by the Wright Group, 1993)
Depicts the wave of Italian immigration to America at the beginning of the twentieth century, describing the life left behind in Italy and the challenges faced in America. Includes brief discussions of some prominent Italian Americans.
Includes bibliographical references (p. 46) and index.
Keywords: Italian Americans -- History -- Juvenile literature; Italian Americans -- History; United States -- Emigration and immigration